A New Species of the Genus Leistus (Coleoptera, Carabidae) from China - Belousov, I.A.; Kabak, I.I. (Вестник зоологии, 2000)
Leistus (Evanoleistus) nanshanicus sp. n. from the Qilian Shan Mountain Range (China, prov. Gansu) is described. Its comparision with L. farkaci Sciaky is given. Описан Leistus (Evanoleistus) nanshanicus sp. n. с хребта Циляньшань (Китай, провинция Ганьсу). Приведено его сравнение с L. farkaci Sciaky